2018
DOI: 10.1186/s40413-018-0212-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microbiota and allergen profile in house dust from homes of allergic and non-allergic subjects- results from the GUSTO study

Abstract: BackgroundThe prevalence of allergic diseases, such as asthma, allergic rhinitis, eczema and food allergy, has been increasing worldwide, as shown in a large number of studies, including the International Study of Asthma and Allergies in Childhood (ISAAC). However, there is significant variation in the prevalence of these diseases in different regions, suggesting that there may be location-specific factors such as environment and microbial exposure affecting allergic disease prevalence. Hence, in this study we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…In homes, studies were mostly done on floors, kitchen sinks, and bathrooms [5,11]. However, very little is known about microbial communities present in beds with which humans have extended daily exposure [12].…”
Section: Introductionmentioning
confidence: 99%
“…In homes, studies were mostly done on floors, kitchen sinks, and bathrooms [5,11]. However, very little is known about microbial communities present in beds with which humans have extended daily exposure [12].…”
Section: Introductionmentioning
confidence: 99%
“…One limitation is that this study is cross-sectional, and the results cannot determine causality. To Chinese migrants, the change to a western environment is the combination of a different diet, less air pollution, exposure to new allergens and, greater hygiene, all of which can lead to different microbiota composition/diversity, and contribute to the increased allergies in AC children 33, 34. However, in this study we could only focus on the overall influence of a western environment on the microbiome and the relation with allergy.…”
Section: Discussionmentioning
confidence: 99%
“…36 Similarly, based on the findings from the Growing Up in Singapore Towards healthy Outcomes (GUSTO) birth cohort study, our group has reported that there were differential microbiota and allergen profiles in house dust collected from homes of allergic participants compared to healthy controls. 38 Houses of allergic participants had higher levels of Bacteroidaceae, Anaplasmataceae, and Leptospiraceae, all of which are gram negative. 38 Endotoxins which are associated with gram negative bacteria have also been shown to potentially increase risk of wheezing in children from a Boston study.…”
Section: Environmental Dust and Ncdsmentioning
confidence: 96%
“…38 Houses of allergic participants had higher levels of Bacteroidaceae, Anaplasmataceae, and Leptospiraceae, all of which are gram negative. 38 Endotoxins which are associated with gram negative bacteria have also been shown to potentially increase risk of wheezing in children from a Boston study. 39 Besides this, abundance of Bacteroidaceae was higher in gut microbiota of allergic Japanese subjects at 1 and 2 months of age, as compared to the non-allergic subjects which also suggests a possible link between environmental and gut microbiota.…”
Section: Environmental Dust and Ncdsmentioning
confidence: 96%